A COMPARATIVE STUDY OF CUSTOMER PERCEPTION ABOUT INSURANCE COMPANY WITH SPECIAL REFERENCE TO LIC AND HDFC STANDARD LIFE POLICIES - Nisamudheen. T
Customer service is an integral part of Life insurance organization. It is necessary to identify the key success factors in life insurance industry, in terms of customer satisfaction so as to survive in intense competition and increase the market share. Mainly there are two objectives are involved in this study. Both primary and secondary data’s are used in this study. Primary data’s are collected through personal interviews in the form of questionnaire from a sample of 100 policyholders selected from the Malappuram district, Kerala. For conducting the study 50 LIC customers and 50 HDFCSL customers are selected at a random. The questionnaire prepared on the basis of various factors which influence the satisfaction of the policy holders. The tools used for this study are percentage analysis, weighted average, Analysis of Variance, Chi-square test.